Higher diversity and abundance of microRNA-455-5p isoforms confer suppressive role in Wilms’ tumor - Chen, Cao; Zhou, Zhou; Yao, Chunfang; Li, Xiaowei; Wang, Yifei; Zhou, Xiaogang; Ni, Hengli (Frontiers in Oncology, 2025)
IntroductionMicroRNA isoforms (isomiRs) are differentially expressed across tissues, populations, genders, and various disease states, playing significant roles in tumorigenesis and treatment. However, their expression profiles, functions, and clinical relevance in pediatric Wilms' tumour (WT) remain poorly understood.MethodsUsing small RNA-seq data from the TARGET initiative, we profiled isomiRs in WT and adjacent tissues. Bioinformatics tools identified target genes. Key findings were validated in an independent cohort (n=63) using immunohistochemistry (IHC) and multiplex immunofluorescence combined with fluorescence in situ hybridization (mIF-FISH). Associations with histology and survival were analyzed using Kaplan-Meier and Cox regression models.ResultsOur results revealed that various isoforms of miR-455-5p demonstrated greater diversity and abundance in WT compared to its archetype, and were more closely associated with the tumour. Patients exhibiting a higher variety and number of miR-455-5p isoforms showed superior survival rates, independent of tumour differentiation. Notably, the isoform miR-455-5p 0|1 exhibited enhanced complementarity to its predicted target gene SP100 compared to the archetype, suggesting its potential role in influencing the histological classification of WT through SP100 regulation.DiscussionThis study provides the first comprehensive analysis of isomiRs in WT, identifying miR-455-5p isoform diversity as a novel prognostic indicator. The specific isoform miR-455-5p 0|1 likely exerts a tumour-suppressive role, potentially through a non-canonical regulatory interaction with SP100. These findings unveil isomiR-mediated regulation as a critical layer of molecular complexity in Wilms’ tumour, offering new insights for prognostic stratification.